Potential ecological risk assessment of heavy metals (trace elements) in coastal soils of southwest Iran - Hamid, Ebtessam; Payandeh, Khoshnaz; Karimi Nezhad, Mohammad Tahsin; Saadati, Naghmeh (Frontiers in Public Health, 2022)
Heavy metal pollution has become one of the most important threats that can endanger the health of animals, the environment, and humans. The present study was performed to investigate the potential ecological risk (PER) assessment of heavy metal (Zinc (Zn), Copper (Cu), Cobalt (Co), molybdenum (Mo), manganese (Mn) and selenium (Se)) in the coastal soils of southwest Iran during 2019. The samples were collected from six soil sites and three depth intervals (0-15, 15-30, and 30-45 cm) among bare and vegetated coastal soils. Soil properties (soil grain sizes, pH, EC, and soil organic carbon) and metal samples were taken from soil (36 samples), water (6 samples), and plants (24 samples). Assessment of soil ecological risk (ER), the indices of pollution load index (PLI), contamination degree (Cdeg), modified contamination degree (mCdeg) for heavy metal contamination in the soil, and enrichment factor (EF index) indicate the origin of metals entering the environment were investigated. The result of this study showed that the levels of Zn, Cu, Co, Mn, Se, and Mo were in the range of low-risk contaminants in this region. According to the result of the study, the risk index (RI) for metals was in the range of 1.296 to 3.845, which is much lower than 150, and therefore, the ecological risk potential calculated in this study was in the low-risk category for toxic elements. Based on the results, it was found that agricultural, industrial, and human activities have played an effective role in the accumulation of Zn, Cu, Co, Se, and Mo in the soil. Also, the main source of Mn metal is believed to be natural and geological activities in the region.